Synthesis, structure and gas-phase reactivity of the mixed silver hydride borohydride nanocluster [Ag3(μ3-H)(μ3-BH4)LPh3]BF4 (LPh = bis(diphenylphosphino)methane). Issue 43 (16th October 2015) - Zavras, Athanasios; Ariafard, Alireza; Khairallah, George N.; White, Jonathan M.; Mulder, Roger J.; Canty, Allan J.; O'Hair, Richard A. J.
Abstract : Borohydrides react with silver salts to give products that span multiple scales ranging from discrete mononuclear compounds through to silver nanoparticles and colloids. Abstract : Borohydrides react with silver salts to give products that span multiple scales ranging from discrete mononuclear compounds through to silver nanoparticles and colloids. The cluster cations [Ag3 (H)(BH4 )L3 ] + are observed upon electrospray ionization mass spectrometry of solutions containing sodium borohydride, silver(i ) tetrafluoroborate and bis(dimethylphosphino)methane (L Me ) or bis(diphenylphosphino)methane (L Ph ). By adding NaBH4 to an acetonitrile solution of AgBF4 and L Ph, cooled to ca. −10 °C, we have been able to isolate the first mixed silver hydride borohydride nanocluster, [Ag3 (μ3 -H)(μ3 -BH4 )L Ph 3 ]BF4, and structurally characterise it via X-ray crystallography. Combined gas-phase experiments (L Me and L Ph ) and DFT calculations (L Me ) reveal how loss of a ligand from the cationic complexes [Ag3 (H)(BH4 )L3 ] + provides a change in geometry that facilitates subsequent loss of BH3 to produce the dihydride clusters, [Ag3 (H)2 L n ] + ( n = 1 and 2). Together with the results of previous studies (Girod et al., Chem. – Eur. J., 2014, 20, 16626), this provides a direct link between mixed silver hydride/borohydride nanoclusters, silver hydride nanoclusters, and silver nanoclusters.